LATEST ADVANCES IN INJECTABLE AND ORAL MEDICATIONS FOR TYPE 2 DIABETES TREATMENT - Katarzyna Jurkiewicz; Marek Ciechański; Aleksandra Kasprzyk; Klaudia Wilk; Edyta Witkowska; Szymon Cholewiński; Bernadetta Wilk; Piotr Stachura; Piotr Rejman; Katarzyna Pszczoła (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Type 2 diabetes mellitus (T2DM) is a progressive metabolic disorder characterized by insulin resistance and impaired beta-cell function. Effective management extends beyond glycemic control and includes weight reduction and cardiovascular risk mitigation. In recent years, injectable therapies such as GLP-1 receptor agonists and the novel dual GIP/GLP-1 receptor agonist tirzepatide have shown promising results. These agents offer significant improvements in blood glucose levels, body weight, and cardiometabolic outcomes, positioning them as essential components of modern T2DM treatment strategies. Materials and Methods: This article presents a comprehensive review of literature derived from the PubMed database, encompassing studies published between 2015 and 2025. Results: Recent clinical studies confirm the effectiveness of GLP-1 receptor agonists (GLP-1RAs) and the dual GIP/GLP-1 agonist tirzepatide in managing type 2 diabetes. Long-acting GLP-1RAs, especially semaglutide, show superior HbA1c and weight reduction compared to other agents. Tirzepatide demonstrated even greater efficacy than semaglutide in reducing blood glucose and body weight, along with benefits for blood pressure and lipid levels. Both drugs have similar safety profiles, with mild gastrointestinal side effects. The development of oral semaglutide further enhances treatment options, particularly for patients avoiding injections. Conclusions: Advances in injectable therapies for type 2 diabetes, particularly GLP-1 receptor agonists and the dual GIP/GLP-1 agonist tirzepatide, have significantly improved glycemic control, weight management, and cardiovascular outcomes. Tirzepatide shows greater efficacy than semaglutide in reducing HbA1c and body weight. While safety profiles are favorable, long-term data are still needed. These therapies offer personalized treatment options, supporting better long-term health for people with type 2 diabetes.